Implementation and experimental validation of a robust hybrid direct aperture optimization approach for mixed‐beam radiotherapy. Issue 11 (14th October 2021) - Heath, Emily; Mueller, Silvan; Guyer, Gian; Duetschler, Alisha; Elicin, Olgun; Aebersold, Daniel; Fix, Michael K.; Manser, Peter
Abstract: Purpose: The objectives of the work presented in this paper were to (1) implement a robust‐optimization method for deliverable mixed‐beam radiotherapy (MBRT) plans within a previously developed MBRT planning framework; (2) perform an experimental validation of the delivery of robust‐optimized MBRT plans; and (3) compare PTV‐based and robust‐optimized MBRT plans in terms of target dose robustness and organs at risk (OAR) sparing for clinical head and neck and brain patient cases. Methods: A robust‐optimization method, which accounts for translational setup errors, was implemented within a previously developed treatment planning framework for MBRT. The framework uses a hybrid direct aperture optimization method combining column generation and simulated annealing. A robust plan was developed and then delivered to an anthropomorphic head phantom using the Developer Mode of a TrueBeam linac. Planar dose distributions were measured and compared to the planned dose. Robust‐optimized and PTV‐based plans were developed for three clinical patient cases consisting of two head and neck cases and one brain case. The plans were compared in terms of the robustness to 5 mm shifts of the target volume dose as well as in terms of OAR sparing. Results: Using a gamma criterion of 3%/2 mm and a dose threshold of 10%, the agreement between film measurements and dose calculations was better than 97.7% for the total plan and better than 95.5% for the electron component of the plan. For the two head and neck patient cases, the average clinical target volume (CTV) dose homogeneity index (V95%–V107%) over all the considered setup error scenarios was on average 19% lower for the PTV‐based plans and it had a larger standard deviation. The robust‐optimized plans achieved, on average, a 20% reduction in the OAR doses compared to the PTV‐based plans. For the brain patient case, the CTV dose homogeneity index was similar for the two plans, while the OAR doses were 22% lower, on average, for the robust‐optimized plan. No clear trend in terms of electron contributions was found across the three patient cases, although robust‐optimized plans tended toward higher electron beam energies. Conclusions: A framework for robust optimization of deliverable MBRT plans has been developed and validated. PTV‐based MBRT were found to not be robust to setup errors, while the dose delivered by the robust‐optimized plans were clinically acceptable for all considered error scenarios and had better OAR sparing. This study shows that the robust optimization is a promising alternative to conventional PTV margins for MBRT.